ReS2 vs MoS2: Viable electrodes for batteries and capacitors - Ashish Nadar; Yukti Arora; Pallavi Thakur; T.N. Narayanan; Arnab Bhattacharya; Deepa Khushalani (Electrochemistry Communications, 2022)
Presented is an electrochemical study on a relatively new member of TMDC: ReS2. A systematic study has been done wherein pure ReS2′s viability, as a component in both faradaic and capacitive storage devices, has been found to be superior to the oft-cited conventional TMDC: MoS2. When evaluated as anode for Li-ion batteries, ReS2 showed higher storage capacity as well as better cycling stability. For supercapacitor applications, bulk ReS2 electrode was found to hold two times higher charge than bulk MoS2. Post exfoliation, ReS2 values were augmented by ca. 630% compared to unexfoliated samples. Detailed analysis revealed that several structural variations between ReS2 and MoS2 lead to the superior performance observed. In ReS2, there exists a weaker interlayer coupling, an intrinsic structural anisotropy due to presence of Re-Re interaction, and improved conductivity is prevalent due to interaction between Re chains that cumulatively improve electrochemical performance of ReS2. These attributes provide for robustness of ReS2 under prolonged electrochemical activity and this provides impetus for its use as a more viable alternative for a successful energy storage material.